Environmental Communication of the Public Relations Division of Pt Semen Baturaja Tbk in Response to Air Quality Issues in the Community - Putri Utami; Yenrizal; Muslimin Ritonga (Universitas Muhammadiyah Palu, 2026)
This study aims to find out how the role of Public Relations of PT Semen Baturaja Tbk in carrying out effective environmental communication, so as to be able to maintain public trust in the midst of the dynamics of developing environmental issues. The problem contained in this study is that air pollution due to industrial activities is an environmental issue that is increasingly receiving public attention, especially in areas that are directly adjacent to emission sources. The type of research used is field research with a qualitative approach that is descriptive. The data collection methodology used in this study is observation, documentation and interviews. The primary data sources in this study are the leaders of PT Semen Baturaja Tbk, the Public Relations Division of PT Semen Baturaja and the people who live around PT Semen Batujara Tbk. Meanwhile, the source of secondary data was obtained from documentation obtained from the results of the research. The technique for analyzing data is through three stages, namely: data reduction, data presentation and drawing conclusions or verification. Based on the results of the research, the communication practices carried out have led to dialogical and participatory two-way communication and show a positive tendency in building harmonious relationships between companies and society.